Pandemic Journalism: A Study of Covid-19 News Coverage on detik.com - Benediktus Edi Woda; Mario Antonius Birowo; Irene Santika Vidiadari; Ranggabumi Nuswantoro (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2021)
During a pandemic, people need information as a basis for knowledge and policymaking. This study aimed to describe the news about Covid-19 in the online media detik.com. This research used the quantitative content analysis method. The news from 688 articles with a period from 6 January to 9 March 2020 were collected. Disaster communication was used as a framework for understanding pandemic journalism. Pandemic journalism promoted health by presenting information that is ethical and scientifically based. News coverage during pandemics paid attention to vulnerable groups and expedited handling of pandemics. This study showed that news on detik.com is dominated by direct news 35%, health themes 52%, news with prevention dimensions 53%, and 90% news using scientific terms without any explanation. The news detik.com is still working on presenting pandemic journalism.